Synergistic remediation of oil-water mixtures: integration of nanoparticles and oil-degrading bacteria in a novel approach - El-Sesy, Marwa E.; Ibrahim, Sabah S.; Yang, Fan; Hegazy, Abeer (Frontiers in Microbiology, 2025)
Oil Spillage is considered one of the environmental disasters due to the release of hydrocarbons into the aquatic environment, causing destructive effects. Usually, it occurs accidentally or intentionally, mostly resulting from human activities. Effective degradation of these spills is vital to preserving the aquatic ecosystem. Recently, combining state-of-the-art nanotechnology with degrading bacteria is an area of great interest and opens new paths for addressing oil/water pollution issues. In this context, the current study assesses the synergetic effect of a hybrid of green-synthesized magnetite nanoparticles and oil-degrading bacteria on oil spill removal in vitro conditions. Bacterial isolates were isolated from water samples collected from Sharkia, Qalyubia, and Minufiya Governorates in Egypt. Effective oil-degrading strains were identified by 16S rRNA gene sequencing. Magnetite nanoparticles (AL-MNPs) were synthesized from Artemisia leaf extract through green synthesis and characterized using UV-Vis spectroscopy, TEM, EDX, and FTIR. Bacterial growth was compared with the effect of AL-MNPs at various concentrations and exposure durations. Results indicated that the interaction between AL-MNPs and bacteria greatly enhanced oil degradation. With optimal conditions (35°C, pH 7, 300 mg/l oil, and 0.04 g AL-MNPs), almost 90% of oil was degraded after 3 days. AL-MNPs alone degraded about 59%, and bacteria alone degraded 72–80% in the same period. GC-MS analysis verified that the system degraded almost 50% lower-chain alkanes (C9–C22) and 30% higher-chain alkanes (C23–C26). Furthermore, the recyclability of the AL-MNPs was also explored, with slight loss of removal efficiency upon repeated usage, but with superior performance. This demonstrates the long-term capability of the AL-MNPs-bacteria system. Correspondingly, the eco-friendly synthesis of AL-MNPs using plant extracts reinforces their role as a sustainable and cost-effective alternative to oil spill degradation techniques. The most astounding result, the synergizing effect between oil-degrading bacteria, environmentally isolated, and AL-MNPs. This not only enhances the degradation process but also contributes to a greener, more integrated remediation strategy that aligns with circular economy and environmental protection goals.